ON THE RELATIVELY COMPOSITIONAL HOMOGENEITY OF ALBANIAN EASTERN OPHIOLITIC BELT - Çina Α. (Bulletin of the Geological Society of Greece, 2016)
Ophiolitic formation of Albanides, named as Mirdita zone, represents a compact segment of oceanic lithosphere of Middle-Upper Jurassic. Based on petrographic, geochemical and metalogenical features two types of belts are distinguished: western MORB and eastern SSZ types. In fact, structural and geological units as well as many other elements have shed light on lack of a sharp separation between the two belts. Recent investigations have evidenced that different ultramafic massifs of western ophiolitic formation, represent an evident variation of their composition from harzburgite to lherzolitic -types. This composition reflects a different grade of partial melting of upper mantle. Peridotites show a high variability, from 0.3 - 3.8 wt.% Al2O3, varying from small to highly extreme depleted peridotite. On the contrary, Albanian eastern belt, it seems to be formed by a more homogeneous hartzburgitic mantle. Detailed petrologic and metallogenic investigations have evidenced that this belt changes also from one massif to another, naturally at a smaller level, therefore it is easier to be named relatively homogeneous. It is distinguished by a higher melting degree, chiefly of hartzburgitic-type, characterized by whole and thick ultramafic section, as well as by metalogenic variety, mostly of metallurgic-type of chromite mineralization. It is supposed that rock-forming and mineraluzation processes have been developed not uniformly along the ophiolitic belt.